Seed coat colour as an indicator of physiological seed quality - S. Seethaladevi; M. Kathiravan; C. Vanitha; R. Umarani; G. Preetha; S. Marimuthu; M. K. Sakthi Anand (Plant Physiology Reports, 2026)

Edible synbiotic film based on soy protein reinforced with nanocellulose synthesized from jackfruit residues and probiotic (Lactobacillus pentosus) for feta cheese packaging - B. Pooja; R. Preetha; V. Sreejit; S. Maanila Devi (Food Bioscience, 2026)

Nurses' Knowledge of Hospital Safety in A Tertiary Healthcare Setting - Athirarani M․R․; Ajayan Kamalasanan; Vinoth Raman; Jibina John; Lekshmi R․; Liji C․; Preetha S․; Rejani A․V․; Reshma S․R․; Roshni K․P․ (Next Research, 2025)

Antennal sensilla architecture of Thrips parvispinus (Karny) and Thrips subnudula (Karny) infesting chillies, Capsicum annuum L.: insights from scanning electron microscopy - Chandrasekaran Praveenkumar; Saminathan Vangili Ramasamy; Rachana Rajan Remani; Kesavan Subaharan; Preetha Gnanadhas; Selvam Saravanan; Subrata Goswami; Amala Udayakumar; Vellaikumar Sampathrajan; Kavitha Chinnasamy; S. N. Sushil (Zoomorphology, 2025)

Acoustic detection of Callosobruchus maculatus (F.) (Coleoptera: Chrysomelidae) in green gram and cowpea using MEMS microphone system - B. Keerthana; G. Preetha; K. Umapathi; V. R. Saminathan; T. Eevera; J. Malathi; S. Santhi (Journal of Plant Diseases and Protection, 2025)

Anti-lipidemic and anti-diabetic properties of Gymnema sylvestre saponins: an in-silico approach - R. Archana Preetha; G. Dicky John Davis; M. Gowri Neelima; B. S. Chaitra; B. Kirankumar (In Silico Pharmacology, 2025)

Spatio-temporal monitoring of water quality in the Gharni reservoir (India) by multivariate statistical tools: a case study of a reservoir located in a rainfall deficit area - Vijaykumar B. Sutar; Asha T. Landge; Binaya B. Nayak; Preetha Panikkar; Pachampalayam S. Ananthan; Adinath T. Markad (Environmental Science and Pollution Research, 2025)

Comparative investigation of structural properties and biological applications of chemical and biogenic synthesis of zirconium dioxide (ZrO2) nanoparticles using Passiflora edulis - Preetha S; Anilkumar P; Nisha Jenifar A (Journal of Photochemistry and Photobiology B: Biology, 2025)

Identification and comparative analysis of differential proteins expression in rice under biotic stress by protein sequencing - Subhashini Shinde; P. S. Abida; Manjesh Saakre; Haseena Bhaskar; R. Beena; R. Preetha (Cereal Research Communications, 2024)

Effect of Bacillus thuringiensis B. δ-endotoxin (Cry1Ac) on the biological and life table characteristics of tobacco cutworm, Spodoptera litura F - M. Kannan; A. Nasreen; K. Elango; S. Preetha; K. Govindaraju (International Journal of Tropical Insect Science, 2024)

Effect of Pulsed Light Treatment for the Preservation of Coconut Inflorescence Sap - V. Vishnu Priya; M. Balakrishnan; R. Pandiselvam; S. Karthikeyan; P. Rajkumar; M. R. Manikantan; K. Gurusamy; P. Preetha (Sugar Tech, 2024)

Cryopreservation of shoot meristems of Baliospermum montanum (Willd.) Muell. Arg. for long-term conservation and sustainable utilization - K. P. Parvathi; T. S. Preetha; A. S. Hemanthakumar (Vegetos, 2023)

Comparative analysis of carbon emission from products of virgin plastics and recycled plastics and their environmental benefits - A. Ganesan; H. Preetha; S. Subathara; S. Bhowmik (International Journal of Environmental Science and Technology, 2023)

Usage pattern of chemicals, biologicals and veterinary medicinal products in Indian aquaculture - Prasanna K. Patil; Sudhansu S. Mishra; Pravata K. Pradhan; Sanjib K. Manna; Jawahar T. Abraham; Haresh G. Solanki; Neetu Shahi; Priyabrata Swain; Satya N. Sahoo; Satheesha Avunje; Krupesha S. R. Sharma; Rajamanickam Geetha; et al. (Reviews in Aquaculture, 2022)
The use of chemicals, biologicals and veterinary medicinal products (VMPs) helps in healthy and sustainable fish production. Information on the use of these products is essential for assessing farming practices, potential human health and environmental risks. A questionnaire‐based nationwide survey covering aquaculture farms ( n = 2936) producing carps, tilapia, pangasius and rainbow trout in freshwater and shrimp in brackishwater estimated the use of 52 different types of inputs which included disinfectants (597 g t −1 ), probiotics (2.28 kg t −1 ), environmental modifiers (22.82 kg t −1 ), nutritional supplements (1.96 kg t −1 ), natural anti‐infective agents (293 g t −1 ), herbicide and piscicides (844 g t −1 ), antibiotics (2 mg PCU −1 ), antifungal (4 mg PCU −1 ), and antiparasitic (14 mg PCU −1 ) agents. The bulk of these inputs was used for soil and water quality improvement and had low environmental and human safety concerns. The multivariate analysis revealed significant variation in the frequency and quantity of compounds use among farm groups. Redundancy analysis revealed a significant association between the number of products used and stocking density. The survey also showed a considerable influence of education and farming experience on the usage pattern of aquaculture inputs. Results of the study indicated greater reliance of farmers on the use of disinfectants for biosecurity, nutritional supplements for enhanced growth and environmental modifiers for maintaining soil and water quality in culture systems. Though there was no use of restricted antibiotics and antiparasitic agents, the development and implementation of standard regulatory guidelines are essential for safe and effective use of inputs for sustainable aquaculture.

Phosphorus fractions in the sediment of a tropical reservoir, India: Implications for pollution source identification and eutrophication - Ajoy Saha; P. K. Jesna; V. L. Ramya; S. Sibina Mol; Preetha Panikkar; M. E. Vijaykumar; U. K. Sarkar; B. K. Das (Environmental Geochemistry and Health, 2022)

Evaluation of Spatio-temporal Changes in Surface Water Quality and Their Suitability for Designated Uses, Mettur Reservoir, India - Ajoy Saha; V. L. Ramya; P. K. Jesna; S. Sibina Mol; Preetha Panikkar; M. E. Vijaykumar; U. K. Sarkar; B. K. Das (Natural Resources Research, 2021)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Trends and variability of meteorological drought over the districts of India using standardized precipitation index - P Guhathakurta; Preetha Menon; P M Inkane; Usha Krishnan; S T Sable (Journal of Earth System Science, 2017)

Report from a symposium on catalyzing primary and secondary prevention of cancer in India - Suneeta Krishnan; Preet K. Dhillon; Afsan Bhadelia; Anna Schurmann; Partha Basu; Neerja Bhatla; Praveen Birur; Rajeev Colaco; Subhojit Dey; Surbhi Grover; Harmala Gupta; Rakesh Gupta; et al. (Cancer Causes & Control, 2015)

A New Era of Low-Dose Radiation Epidemiology - Cari M. Kitahara; Martha S. Linet; Preetha Rajaraman; Estelle Ntowe; Amy Berrington de González (Current Environmental Health Reports, 2015)

Optimization of Culture Conditions for Mass Production of the Probiotics Pseudomonas MCCB 102 and 103 Antagonistic to Pathogenic Vibrios in Aquaculture - R. Preetha; K. K. Vijayan; N. S. Jayapraksh; S. V. Alavandi; T. C. Santiago; I. S. Bright Singh (Probiotics and Antimicrobial Proteins, 2015)

Modulation of PPARγ and TNFα by emu oil and glycyrrhizin in ulcerative colitis - Sri Nandhini Sethuraman; Selvasubramanian Swaminathan; Shinu B. Nelson; Preetha S. Palaninathan; Tirumurugaan K. Gopalan; Pandiyan Velayudham (Inflammopharmacology, 2015)

Parmotrema tinctorum exhibits antioxidant, antiglycation and inhibitory activities against aldose reductase and carbohydrate digestive enzymes: an in vitro study - P. Salin Raj; A. Prathapan; Jomon Sebastian; Antu K. Antony; Mariam Philip Riya; M.R. Preetha Rani; H. Biju; S. Priya; K.G. Raghu (Natural Product Research, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

Diazotrophic diversity in the rhizosphere of two exotic weed plants, Prosopis juliflora and Parthenium hysterophorus - B. Cibichakravarthy; R. Preetha; S. P. Sundaram; K. Kumar; D. Balachandar (World Journal of Microbiology and Biotechnology, 2012)

The impact of delayed blood centrifuging, choice of collection tube, and type of assay on 25-hydroxyvitamin D concentrations - Chu-Ling Yu; Roni T. Falk; Michael G. Kimlin; Preetha Rajaraman; Alice J. Sigurdson; Ronald L. Horst; Louis M. Cosentino; Martha S. Linet; D. Michal Freedman (Cancer Causes & Control, 2010)

Toxicity of selected insecticides to Trichogramma chilonis: Assessing their safety in the rice ecosystem - G. Preetha; J. Stanley; S. Suresh; S. Kuttalam; R. Samiyappan (Phytoparasitica, 2009)

Cancer is a Preventable Disease that Requires Major Lifestyle Changes - Preetha Anand; Ajaikumar B. Kunnumakkara; Chitra Sundaram; Kuzhuvelil B. Harikumar; Sheeja T. Tharakan; Oiki S. Lai; Bokyung Sung; Bharat B. Aggarwal (Pharmaceutical Research, 2008)

Cancer is a Preventable Disease that Requires Major Lifestyle Changes - Preetha Anand; Ajaikumar B. Kunnumakara; Chitra Sundaram; Kuzhuvelil B. Harikumar; Sheeja T. Tharakan; Oiki S. Lai; Bokyung Sung; Bharat B. Aggarwal (Pharmaceutical Research, 2008)

Influence of Changes in the Prevailing Synoptic Conditions on the Response of Aerosol Characteristics to Land- and Sea-Breeze Circulations at a Coastal Station - K. Krishna Moorthy; Preetha S. Pillai; S. Suresh Babu (Boundary-Layer Meteorology, 2003)

Purification and characterization of a milk clotting protease from Rhizomucor miehei - S. Preetha; R. Boopathy (World Journal of Microbiology and Biotechnology, 1997)